Perbandingan Hasil Belajar Menggunakan Model Everyone is a Teacher Here dan Make a Match - Vevi Liasari; Sudjarwo Sudjarwo; Edy Purnomo (Jurnal Studi Sosial / Journal of Social Studies, 2017)
This study aimed to compare the learning outcomes of students on the subjects of geography XI in high schools 10 Bandar Lampung. The purpose of this research is that is to knowing the difference learning outcomes of students, between students who use the model of learning everyone is a teacher here with students who use the learning model make a match that was given the assignment and project portfolio. Research method used is experiment with specious approach. Engineering data collection is done through poll and tests. To test instrument use the validity, test reliability, the trouble, and the different.Analysis techniques data using analysis variant two roads and the hypothesi. The research results show that the difference study results students, between students who use learning model everyone is a teacher here with students who use learning model make a match given the assignment portfolio and project.Penelitian ini dilatarbelakangi masalah rendahnya hasil belajar siswa pada mata pelajaran Geografi XI semester ganjil di SMA Negeri 10 Bandar Lampung. Tujuan penelitian ini adalah yaitu untuk mengetahui perbedaan hasil belajar siswa, antara siswa yang menggunakan model pembelajaran Everyone Is A Teacher Here dengan siswa yang menggunakan model pembelajaran Make A Match yang diberi Penugasan Portofolio dan Proyek. Metode penelitian yang digunakan adalah dengan pendekatan eksperimen semu. Teknik pengumpulan data dilakukan melalui angket dan tes. Untuk uji instrument menggunakan uji validitas, reliabilitas tes, tingkat kesukaran, dan daya beda. Teknik analisis data menggunakan analisis varian dua jalan dan uji t. Hasil Penelitian menunjukkan bahwa ada perbedaan hasil belajar siswa, antara siswa yang menggunakan model pembelajaran Everyone Is A Teacher Here dengan siswa yang menggunakan model pembelajaran Make A Match yang diberi Penugasan Portofolio dan Proyek.Kata kunci: Model Pembelajaran, Hasil Belajar, dan Penugasan.